Nursing Home Residents With Dementia: Association Between Place of Death and Patient Safety Culture. (18th November 2020) - Orth, Jessica; Li, Yue; Simning, Adam; Zimmerman, Sheryl; Temkin-Greener, Helena
Abstract: Background and Objectives: Nursing homes (NHs) care for 70% of Americans dying with dementia. Many consider deaths in NHs rather than hospitals as preferable for most of these residents. NH characteristics such as staff teamwork, communication, and other components of patient safety culture (PSC), together with state minimum NH nurse staffing requirements, may influence location of death. We examined associations between these variables and place of death (NH/hospital) among residents with dementia. Research Design and Methods: Cross-sectional study of 11, 957 long-stay NH residents with dementia, age 65+, who died in NHs or hospitals shortly following discharge from one of 800 U.S. NHs in 2017. Multivariable logistic regression systematically estimated effects of PSC on odds of in-hospital death among residents with dementia, controlling for resident, NH, county, and state characteristics. Logistic regressions also determined moderating effects of state minimum NH nurse staffing requirements on relationships between key PSC domains and location of death. Results: Residents with dementia in NHs with higher PSC scores in communication openness had lower odds of in-hospital death. This effect was stronger in NHs located in states with higher minimum NH nurse staffing requirements. Discussion and Implications: Promoting communication openness in NHs across nursing disciplines may help avoid unnecessary hospitalization at the end of life, and merits particular attention as NHs address nursing staff mix while adhering to state staffing requirements. Future research to better understand unintended consequences of staffing requirements is needed to improve end-of-life care in NHs.